2006
DOI: 10.1002/ajmg.a.31423
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Angelman syndrome and Prader–Willi syndrome in Estonian children: Sister syndromes not equally represented

Abstract: In 2000-2004, we performed a focused search for individuals with Angelman syndrome (AS) and Prader-Willi syndrome (PWS) aiming to establish the prevalence data for the individuals born between 1984 and 2004 in Estonia. All persons with probable AS or PWS (n = 184) were studied using the DNA methylation test. Individuals with abnormal methylation were all further tested by chromosomal and FISH analysis, and if necessary for uniparental disomy and UBE3A gene mutation. Nineteen cases with abnormal methylation tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 43 publications
(37 reference statements)
5
22
3
Order By: Relevance
“…This figure is in accordance with the estimate quoted by Clayton‐Smith and Pembrey [], but significantly lower than the estimate of 1:10,000 in a previous Danish epidemiological study [Petersen et al, ]. However, that study only included a birth population of 45,000, compared to the present birth population of more than 1,250,000, which, to the best of our knowledge, also represents the largest population‐based incidence study of AS ever published [Oiglane‐Shlik et al, ; Thomson et al, ]. The proportional percentage distribution of 15q11.2–q13 deletions, pUPD, and UBE3A mutations corresponds to the findings of previous studies [Ruggieri and McShane, ; Fiumara et al, ; Tan et al, ; Dagli et al, ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This figure is in accordance with the estimate quoted by Clayton‐Smith and Pembrey [], but significantly lower than the estimate of 1:10,000 in a previous Danish epidemiological study [Petersen et al, ]. However, that study only included a birth population of 45,000, compared to the present birth population of more than 1,250,000, which, to the best of our knowledge, also represents the largest population‐based incidence study of AS ever published [Oiglane‐Shlik et al, ; Thomson et al, ]. The proportional percentage distribution of 15q11.2–q13 deletions, pUPD, and UBE3A mutations corresponds to the findings of previous studies [Ruggieri and McShane, ; Fiumara et al, ; Tan et al, ; Dagli et al, ].…”
Section: Discussionsupporting
confidence: 88%
“…Eighty‐ninety percent of patients with AS are reported to have epileptic seizures [Williams et al, ; Conant et al, ]. The birth incidence of AS is estimated at between 1:10,000 and 1:40,000 [Petersen et al, ; Buckley et al, ; Oiglane‐Shlik et al, ; Thomson et al, ]. However, previous reports included only a limited number of patients, contained individuals without a genetically verified diagnosis, or were prone to ascertainment bias.…”
Section: Introductionmentioning
confidence: 99%
“…Our finding may reflect the genetic background of Manitoba's population and the study design, which included all patients with chronic ataxia irrespective of the cause of their disorder. The birth prevalence of Angelman syndrome, in which ataxia is commonly reported, was approximately 2.5 in 100 000 in Western Australia from 1953 to 2003, 1.9 in 100 000 in Estonia from 1984 to 2004, and ranged between 1.6 and 10 with an average of about 5 in 100 000 in previous studies . In our study, the crude period prevalence rate of 5.9 in 100 000 for Angelman syndrome during the study period is in the same reported range.…”
Section: Discussionsupporting
confidence: 84%
“…The birth prevalence of Angelman syndrome, in which ataxia is commonly reported, was approximately 2.5 in 100 000 in Western Australia from 1953 to 2003, 13 1.9 in 100 000 in Estonia from 1984 to 2004, and ranged between 1.6 and 10 with an average of about 5 in 100 000 in previous studies. 14 In our study, the crude period prevalence rate of 5.9 in 100 000 for Angelman syndrome during the study period is in the same reported range. The crude period prevalence rate of Friedreich ataxia during the whole study period was 2.6 in 100 000, which is similar to the prevalence rates reported in Caucasians.…”
Section: Discussionsupporting
confidence: 82%
“…Angelman syndrome (AS) is a rare neurodevelopmental disorder with recent estimates of its prevalence being between 1:22,000 and 1:52,000 [Oiglane‐Shlik et al, ; Mertz et al, ; Luk and Lo, ], although previous studies had suggested that the prevalence was about 1 in 10,000 to 1 in 20,000 [Kyllerman, ; Petersen et al, ; Buckley et al, ]. Individuals with AS have global developmental delay that evolves to severe intellectual disability, with their language skills being more delayed than their motor skills, and their expressive language being far more delayed than their receptive language, usually having only minimal speech.…”
Section: Introductionmentioning
confidence: 99%